The Role of Digital Marketing in Shaping Students’ Attitudes towards Health Care Professions - Santos, Angelo R. (International Review of Management and Marketing, 2024)
Amidst a burgeoning digital landscape, the role of digital marketing in shaping students’ attitudes towards healthcare professions remains relatively unexplored. This study aimed to investigate how digital marketing influences students’ perspectives about healthcare careers, with a specific focus on students in Nueva Ecija, Philippines. Utilizing a quantitative approach, the study involved a survey of 148 students from Nueva Ecija, Philippines. Respondents were asked about their exposure to various forms of digital marketing and their attitudes towards healthcare professions. The study revealed a significant relationship between students’ exposure to digital marketing and their attitudes towards healthcare professions. Notably, higher levels of digital marketing exposure were associated with more positive attitudes towards healthcare careers. Additionally, the findings suggest that targeted advertising campaigns and engaging social media content play a crucial role in shaping these attitudes. The study underscores the potential of digital marketing in addressing the challenges of healthcare workforce shortages and uneven distribution. It highlights the need for educational institutions, healthcare organizations, and policymakers to harness digital marketing strategies effectively to enhance the appeal of healthcare professions among potential students and professionals.